Electrolyte composition, solid electrolyte membrane, composite electrolyte membrane and preparation method thereof, and battery

By using inorganic electrolyte compositions with specific particle size and mass percentages, a high-performance solid electrolyte membrane is formed, which solves the problem of low circulation performance of solid lithium batteries and improves battery energy density and safety.

CN119920956AActive Publication Date: 2025-05-02SHENZHEN INX ENERGY TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510404405.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2025-05-02
Estimated Expiration
2045-04-01

AI Technical Summary

Technical Problem

The existing solid-state lithium batteries have low cycling performance and need to improve their energy density and safety.

Method used

An electrolyte composition, including a specific range of inorganic electrolytes, is used to form a solid electrolyte membrane with high ionic conductivity and good mechanical properties by adjusting its particle size and mass percentage. The electrolyte composition may also contain an ionic liquid and a binder to further improve the performance of the electrolyte membrane.

Benefits of technology

It significantly improves the cycling performance of solid-state lithium batteries, improves the ionic conductivity and mechanical strength of the electrolyte membrane, and reduces the risk of cracks and fractures during use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920956A_ABST
    Figure CN119920956A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides an electrolyte composition, a solid electrolyte membrane, a composite electrolyte membrane and a preparation method thereof, and a battery. The electrolyte composition includes an inorganic electrolyte. The inorganic electrolyte includes a first inorganic electrolyte and a second inorganic electrolyte. The average particle size of the first inorganic electrolyte is 300 nm to 800 nm. The second inorganic electrolyte has an average particle size of 1 [mu] m to 10 [mu] m. In the inorganic electrolyte, the mass percent of the first inorganic electrolyte is 60%-80%, and the mass percent of the second inorganic electrolyte is 20%-40%. Thus, the first inorganic electrolyte and the second inorganic electrolyte cooperate with each other in a proper mass percentage, namely, the mass percentage of the first inorganic electrolyte is greater than that of the second inorganic electrolyte, so that the ionic conductivity of the electrolyte membrane is improved, and rapid migration of lithium ions is facilitated; and the risk of cracks and even breakage of the electrolyte in the use process is reduced, so that the cycle performance of the solid-state lithium battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrolyte technology, and in particular to an electrolyte composition, a solid electrolyte membrane, a composite electrolyte membrane and a preparation method thereof, and a battery. Background Art

[0002] Solid-state lithium batteries have been widely used in various portable electronic devices. The rise of new energy vehicles has promoted significant progress in lithium battery technology. Considering the current range anxiety of new energy vehicles, it is of great significance to develop the next generation of high energy density and high safety batteries.

[0003] At present, how to improve the cycle performance of solid-state lithium batteries is a problem that needs to be solved. Summary of the invention

[0004] In view of this, the embodiments of the present application provide an electrolyte composition, a solid electrolyte membrane, a composite electrolyte membrane and a preparation method thereof, and a battery to ensure the ionic conductivity and mechanical properties of the solid electrolyte membrane prepared from the electrolyte composition, thereby improving the cycle performance of the solid-state lithium battery.

[0005] To achieve the purpose of the present application, according to the first aspect of the embodiment of the present application, an electrolyte composition is provided, wherein the electrolyte composition includes an inorganic electrolyte. The inorganic electrolyte includes a first inorganic electrolyte and a second inorganic electrolyte. The average particle size of the first inorganic electrolyte is 300nm~800nm. The average particle size of the second inorganic electrolyte is 1μm~10μm. In the inorganic electrolyte, the mass percentage of the first inorganic electrolyte is 60%~80%, and the mass percentage of the second inorganic electrolyte is 20%~40%.

[0006] According to a second aspect of an embodiment of the present application, a solid electrolyte membrane is provided, wherein the solid electrolyte membrane comprises the electrolyte composition described in the first aspect.

[0007] According to a third aspect of an embodiment of the present application, a composite electrolyte membrane is provided, wherein the composite electrolyte membrane comprises the solid electrolyte membrane and a polymer electrolyte membrane as described in the second aspect, wherein the polymer electrolyte membrane and the solid electrolyte membrane are stacked.

[0008] According to a fourth aspect of an embodiment of the present application, a method for preparing the composite electrolyte membrane according to the third aspect is provided, comprising: forming a solid electrolyte membrane; forming a polymer electrolyte membrane; The solid electrolyte membrane and the polymer electrolyte membrane are stacked to obtain the composite electrolyte membrane.

[0009] According to a fifth aspect of the embodiment of the present application, a battery is provided, comprising a positive electrode, a negative electrode and a composite electrolyte membrane as described in the third aspect. The composite electrolyte membrane is located between the positive electrode and the negative electrode, and the polymer electrolyte membrane is located between the solid electrolyte membrane and the negative electrode.

[0010] In the electrolyte composition, solid electrolyte membrane, composite electrolyte membrane and preparation method thereof, and battery of some embodiments of the present application, the average particle size of the first inorganic electrolyte is 300nm~800nm, so that the average particle size of the first inorganic electrolyte is small, and more first inorganic electrolytes can increase the number of ion transmission surfaces inside the electrolyte membrane and increase the transmission path of ions. The average particle size of the second inorganic electrolyte is 1μm~10μm, so that the average particle size of the second inorganic electrolyte is larger, which can form a better network structure in the polymer matrix, which is conducive to the rapid migration of lithium ions and improves the film forming property and mechanical properties of the electrolyte membrane. In the inorganic electrolyte, the first inorganic electrolyte and the second inorganic electrolyte cooperate with a suitable mass percentage, that is, the mass percentage of the first inorganic electrolyte is greater than the mass percentage of the second inorganic electrolyte, which improves the ionic conductivity of the electrolyte membrane, helps the rapid migration of ions, and reduces the risk of cracks or even fractures in the electrolyte during use, thereby improving the cycle performance of the solid-state lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 A schematic diagram of the structure of a solid electrolyte membrane provided in some embodiments of the present application; Figure 2 A schematic structural diagram of a composite electrolyte membrane provided for some embodiments of the present application; Figure 3 A schematic structural diagram of another composite electrolyte membrane provided for some embodiments of the present application. DETAILED DESCRIPTION

[0012] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0013] In a first aspect, an embodiment of the present application provides an electrolyte composition. The electrolyte composition includes an inorganic electrolyte. The inorganic electrolyte includes a first inorganic electrolyte and a second inorganic electrolyte. The average particle size of the first inorganic electrolyte is 300nm~800nm. The average particle size of the second inorganic electrolyte is 1μm~10μm. In the inorganic electrolyte, the mass percentage of the first inorganic electrolyte is 60%~80%, and the mass percentage of the second inorganic electrolyte is 20%~40%.

[0014] The average particle size of the first inorganic electrolyte is 300nm~800nm, which makes the average particle size of the first inorganic electrolyte smaller. More first inorganic electrolyte can increase the number of ion transmission surfaces inside the electrolyte membrane and increase the ion transmission path. The average particle size of the second inorganic electrolyte is 1μm~10μm, which makes the average particle size of the second inorganic electrolyte larger. It can form a better network structure in the polymer matrix, which is conducive to the rapid migration of ions and improves the film forming property and mechanical properties of the electrolyte membrane. In the inorganic electrolyte, the first inorganic electrolyte and the second inorganic electrolyte cooperate with a suitable mass percentage, that is, the mass percentage of the first inorganic electrolyte is greater than the mass percentage of the second inorganic electrolyte, which improves the ionic conductivity of the electrolyte membrane, helps the rapid migration of ions, and reduces the risk of cracks or even breaks in the electrolyte during use, thereby improving the cycle performance of the solid-state lithium battery.

[0015] It should be noted that the average particle size of the inorganic electrolyte can be measured by a laser particle size analyzer or a scanning electron microscope. For example, the average particle size of the inorganic electrolyte can be measured by a laser particle size analyzer.

[0016] In some embodiments, the average particle size of the first inorganic electrolyte is 400nm~700nm, and the average particle size of the second inorganic electrolyte is 4μm~8μm, so as to optimize the average particle size of the first inorganic electrolyte and the average particle size of the second inorganic electrolyte, further improve the ionic conductivity of the electrolyte membrane, facilitate the rapid migration of ions, and reduce the risk of cracks or even breakage of the electrolyte during use, thereby improving the cycle performance of the solid-state lithium battery.

[0017] In some embodiments, the average particle size of the first inorganic electrolyte is 500 nm to 800 nm, and the average particle size of the second inorganic electrolyte is 4 μm to 10 μm.

[0018] It is understood that the average particle size of the first inorganic electrolyte can be one or more values ​​in the range of 300 nm to 800 nm, such as 300 nm, 400 nm, 500 nm, 600 nm, 700 nm or 800 nm. The average particle size of the second inorganic electrolyte can be one or more values ​​in the range of 1 μm to 10 μm, such as 4 μm, 5 μm, 6 μm, 7 μm or 8 μm.

[0019] In some embodiments, in the inorganic electrolyte, the mass percentage of the first inorganic electrolyte is 65%~75%, and the mass percentage of the second inorganic electrolyte is 25%~35%, so as to optimize the mass percentage of the first inorganic electrolyte and the second inorganic electrolyte, further improve the ionic conductivity of the electrolyte membrane, and thus further improve the cycle performance of the solid-state lithium battery.

[0020] In some embodiments, in the inorganic electrolyte, the mass percentage of the first inorganic electrolyte is 70%~80%, and the mass percentage of the second inorganic electrolyte is 20%~30%, so as to optimize the mass percentage of the first inorganic electrolyte and the second inorganic electrolyte, further improve the ionic conductivity of the electrolyte membrane, and thus further improve the cycle performance of the solid-state lithium battery.

[0021] It can be understood that the mass percentage of the first inorganic electrolyte can be any value between 60% and 80%, for example, 60%, 65%, 70%, 75% or 80%; the mass percentage of the second inorganic electrolyte can be any value between 20% and 40%, for example, 20%, 25%, 30%, 35% or 40%.

[0022] In some embodiments, the inorganic electrolyte includes an inorganic oxide electrolyte, and the inorganic oxide electrolyte includes one or more of a perovskite material, a NASICON material, and a garnet material, so as to ensure that the inorganic electrolyte has the advantages of high ionic conductivity, a wide electrochemical stability window, and excellent anti-lithium stability.

[0023] In some embodiments, the perovskite material includes Li a La b Ti c A d O e , where 0< a ≤0.5,0< b <0.6,0.9< c ≤1,0≤ d ≤0.25,2< e ≤3, A includes one or more of Ba, Sr, and Al.

[0024] In some embodiments, the perovskite material includes Li 0.5 La 0.5 TiO3、Li 0.29 La 0.57 TiO3、Li 0.30 La 0.57 TiO3、Li 0.33 La 0.56 TiO3、Li 0.34 La 0.51 TiO 2.94 , Li 0.30 La 0.567 TiO3、Li 0.36 Sr 0.04 La 0.523 TiO3、Li 0.33 Ba 0.25 La 0.39 TiO3 and (Li 0.33 La 0.56 ) 1.005 Ti 0.99 Al 0.01 One or more of O3.

[0025] In some embodiments, the NASICON-type material includes Li f B g P h O 12 , where 1≤ f ≤3,0< g ≤4, 1≤ h ≤3, B includes one or more of Al, Zr, Ti, Ge, and Si.

[0026] In some embodiments, NASICON-type materials include LiZr2(PO4)3, LiTi2(PO4)3, and LiGe2(PO4)3, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 (LATP), Li 1.5 Al 0.5 Ge 1.5 (PO4)3 (LAGP), Li3Zr2Si2PO 12 , Li 1.5 Al 0.5 Ge 1.5 (PO4)3、Li 1.4 Al 0.4 Ti 1.6 (PO4)3、Li 1.5 Al 0.5 Ti 1.5 (PO4)3 and Li1.4 Ti2Si 0.4 P 2.6 O 12 -One or more of AIPO4.

[0027] In some embodiments, the garnet-type material includes Li i La j Zr k M l O 12 , where 5≤ i ≤7, 2≤ j ≤3, 1≤ k ≤2,0≤ l ≤1, M is selected from any one of Ta, Nb, Hf, Al, Si, Ga, Sc, Ti, V, Y and Sn.

[0028] In some embodiments, the garnet-type material includes Li 6.4 LqCy 1.4 Ta 0.6 O 12 、Li7La3Zr2O 12 LLZO, Li 6.5 LqCy 1.5 Nb 0.5 O 12 , Li 6.5 LqCy 1.5 Ta 0.5 O 12 , Li 6.375 LqCy 1.375 Nb 0.625 O 12 , Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 , Li 5.9 Al 0.2 LqCy 1.75 W 0.25 O 12 and Li7La 2.75 Ca 0.25 Zr 1.75 Nb 0.25 O 12 One or more of the .

[0029] In some embodiments, the electrolyte composition further comprises an ionic liquid. The ionic liquid comprises at least one of a first ionic liquid and a second ionic liquid. The first ionic liquid comprises a 1-benzyl-3-methylimidazolium cation. The second ionic liquid comprises a 1-ethyl-3-methylimidazolium cation. Due to its larger volume and more complex molecular structure, the 1-benzyl-3-methylimidazolium cation can provide more transmission paths for lithium ions, and these transmission paths ensure that the lithium ions in the inorganic electrolyte are transmitted more smoothly. The 1-ethyl-3-methylimidazolium cation has a higher ionic conductivity for lithium ions.

[0030] In some embodiments, the ionic liquid includes a first ionic liquid and a second ionic liquid. The mass ratio of the inorganic electrolyte, the first ionic liquid and the second ionic liquid is (80-90): (0.6-0.9): (0.6-0.9). Thus, in the electrolyte composition, the 1-benzyl-3-methylimidazolium cation, the 1-ethyl-3-methylimidazolium cation and the inorganic electrolyte are compounded in an appropriate ratio in the electrolyte membrane, which can improve the transport performance of lithium ions in the inorganic electrolyte, thereby improving the cycle performance of the battery.

[0031] In some embodiments, the mass ratio of the inorganic electrolyte, the first ionic liquid, and the second ionic liquid is (80-90): (0.65-0.85): (0.65-0.85).

[0032] In some embodiments, the molar ratio of the cations of the first ionic liquid to the cations of the second ionic liquid is greater than or equal to 0.8 and less than 1. In this way, the cations of the second ionic liquid in the electrolyte membrane have a suitable molar ratio with the cations of the first ionic liquid, and the content of the cations of the second ionic liquid is higher, which increases the ionic conductivity of lithium ions in the inorganic electrolyte, and can improve the transport performance of lithium ions in the inorganic electrolyte, thereby improving the cycle performance of the battery.

[0033] In some embodiments, the anion of the first ionic liquid and the anion of the second ionic liquid are independently selected from one or more of bis(trifluoromethanesulfonyl)imide (NTf2), bis(fluorosulfonyl)imide, bistrifluoromethanesulfonate and trifluoromethanesulfonate (TFO). In this way, the fluorine element in the anion of the first ionic liquid and the anion of the second ionic liquid can react with the lithium element of the negative electrode, promote the formation of a solid electrolyte interface including LiF, effectively inhibit the formation of lithium dendrites, and thus improve the stability of the negative electrode of the solid-state lithium battery.

[0034] In some embodiments, the first ionic liquid may include 1-benzyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (BzmimTFSI) (CAS No.: 433337-24-7), thereby ensuring that the first ionic liquid provides more transport paths for lithium ions and promotes the formation of a solid electrolyte interface including LiF.

[0035] In some embodiments, the second ionic liquid can be selected from one or more of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (CAS No.: 174899-82-2), 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (CAS No.: 35789-75-0) and 1-ethyl-3-methylimidazolium trifluoromethanesulfonate (CAS No.: 145022-44-2). In this way, the second ionic liquid is ensured to have a higher ionic conductivity for lithium ions and promotes the formation of a solid electrolyte interface including LiF.

[0036] In some embodiments, the electrolyte composition may further include a first lithium salt. The first lithium salt includes a fluorine-containing lithium salt. Thus, the fluorine-containing lithium salt promotes the formation of a solid electrolyte interface including LiF, further effectively inhibits the formation of lithium dendrites, and improves the stability of the negative electrode of the solid-state lithium battery.

[0037] In some embodiments, the fluorine-containing lithium salt is selected from one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate, and lithium hexafluorophosphate. Optionally, the fluorine-containing lithium salt includes lithium bis(fluorosulfonyl)imide, so that the first lithium salt has a higher ionic conductivity in the electrolyte, which helps to improve the charge and discharge rate and overall performance of the battery. In addition, the first lithium salt has good thermal stability.

[0038] In some embodiments, the mass ratio of the fluorine-containing lithium salt to the inorganic electrolyte is 1:(80-90). In this way, the fluorine-containing lithium salt and the inorganic electrolyte cooperate in a suitable ratio to ensure the conductivity of the solid electrolyte to lithium ions, while promoting the fluorine element in the fluorine-containing lithium salt to promote the formation of a solid electrolyte interface including LiF, further effectively inhibiting the formation of lithium dendrites, and improving the stability of the negative electrode of the solid-state lithium battery.

[0039] In some embodiments, the electrolyte composition may also include fluorine-containing ester compounds. The fluorine element of the fluorine-containing ester compound promotes the formation of a solid electrolyte interface including LiF, further effectively inhibits the formation of lithium dendrites, and improves the stability of the negative electrode. The fluorine atoms of the fluorine-containing ester compound have an electron-withdrawing effect, thereby promoting the dissociation of the first lithium salt, constructing an ion transmission path in the electrolyte, promoting the transmission of lithium ions, effectively improving the voltage range of the electrolyte membrane, and improving the ionic conductivity of the electrolyte membrane. In addition, the fluorine-containing ester compound is an organic substance with good flexibility and good affinity with the electrode, which can reduce the impedance of lithium ions at the electrode interface, strengthen the close contact between the electrolyte membrane and the electrode, and improve the cycle stability of the battery. In addition, the fluorine-containing ester compound also has high thermal stability, a wide electrochemical stability window and low viscosity performance, which can further improve the performance and safety of the battery.

[0040] In some embodiments, the mass ratio of the fluorinated ester compound to the inorganic electrolyte is (1.5-2.5): (80-90). In this way, the fluorinated ester compound and the inorganic electrolyte work together in a suitable ratio to effectively inhibit the formation of lithium dendrites and improve the stability of the negative electrode.

[0041] In some embodiments, the fluorine-containing ester compound includes hexafluorobutyl methacrylate.

[0042] The electrolyte composition also includes a binder. The binder connects the particles of the inorganic electrolyte and enhances the compactness between the particles of the inorganic electrolyte. In some embodiments, the binder includes at least one of polyethylene oxide and a fluorine-containing polymer.

[0043] In some embodiments, the binder includes polyethylene oxide and a fluoropolymer. Fluoropolymers have good mechanical properties, chemical stability and thermal stability, and can reduce the interfacial impedance between the electrolyte and the electrode. Polyethylene oxide has a high ionic conductivity for lithium ions. When polyethylene oxide is compounded with a fluoropolymer, the two penetrate each other to form a three-dimensional network polymer. The three-dimensional network polymer better connects multiple particles of the inorganic electrolyte, enhancing the structural stability and compactness of the inorganic electrolyte. In addition, the compounding of polyethylene oxide and fluoropolymers can also improve the ionic conductivity of the electrolyte.

[0044] In some embodiments, the mass ratio of the inorganic electrolyte, polyethylene oxide and the fluorinated polymer is (80-90): (0.1-2): (5-9). In this way, the inorganic electrolyte, polyethylene oxide and the fluorinated polymer cooperate in a suitable ratio to enhance the structural stability and compactness of the inorganic electrolyte, while improving the ionic conductivity of the inorganic electrolyte to lithium ions. In addition, the mass of the fluorinated polymer is greater than the mass of the polyethylene oxide, which improves the mechanical properties and stability of the inorganic electrolyte.

[0045] In some embodiments, the mass ratio of the inorganic electrolyte, polyethylene oxide and the fluorinated polymer is (80-90): (1-2): (6-8). In this way, the inorganic electrolyte, polyethylene oxide and the fluorinated polymer cooperate in a suitable ratio to enhance the structural stability and compactness of the inorganic electrolyte, while improving the ionic conductivity of the inorganic electrolyte to lithium ions. In addition, the mass of the fluorinated polymer is greater than the mass of the polyethylene oxide, which improves the mechanical properties and stability of the inorganic electrolyte.

[0046] In some embodiments, the mass ratio of the inorganic electrolyte, polyethylene oxide and fluorine-containing polymer is (80-90): (1-2): (6.5-7.5).

[0047] In some embodiments, the fluoropolymer includes polyvinylidene fluoride. The fluoropolymer is selected from one or more of polyvinylidene fluoride, poly(vinylidene fluoride-trifluoroethylene) P(VDF-TrFE) and poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) P(VDF-TrFE-CFE). Optionally, the fluoropolymer includes poly(vinylidene fluoride-trifluoroethylene).

[0048] In some embodiments, when the fluorine-containing polymer includes poly(vinylidene fluoride-trifluoroethylene), the molar ratio of vinylidene fluoride to trifluoroethylene in the poly(vinylidene fluoride-trifluoroethylene) is (75-85):(15-25). In this way, the mechanical strength and thermal stability of the poly(vinylidene fluoride-trifluoroethylene) are improved, and the interface properties between the electrolyte membrane and the electrode are improved.

[0049] In some embodiments, the weight average molecular weight of the fluorine-containing polymer is 450,000 to 1,100,000. Alternatively, the weight average molecular weight of the fluorine-containing polymer is 500,000 to 1,000,000.

[0050] In some embodiments, the relative molecular weight of polyethylene oxide is 7,500,000-8,500,000.

[0051] Second, as Figure 1 As shown, the embodiment of the present application also provides a solid electrolyte membrane 10, including the above-mentioned electrolyte composition. The first inorganic electrolyte and the second inorganic electrolyte of different particle sizes are coordinated at an appropriate mass percentage, that is, the mass percentage of the first inorganic electrolyte is greater than the mass percentage of the second inorganic electrolyte, so as to improve the ion conductivity of the electrolyte membrane, facilitate the rapid migration of lithium ions, and reduce the risk of cracks or even breakage of the electrolyte during use.

[0052] Thirdly, Figure 2As shown, the embodiment of the present application also provides a composite electrolyte membrane 100, which includes the above-mentioned solid electrolyte membrane 10 and polymer electrolyte membrane 20. The polymer electrolyte membrane 20 is stacked with the solid electrolyte membrane 10. Compared with the solid electrolyte membrane, the polymer electrolyte membrane 20 has good flexibility and can effectively construct a stable negative electrode-electrolyte interface, while the solid electrolyte membrane 10 corresponds to the positive electrode of the battery. Since the voltage window of the solid electrolyte membrane 10 is high, the deterioration of the positive electrode interface under the high voltage of the positive electrode can be effectively alleviated. Therefore, the composite electrolyte membrane formed by combining the polymer electrolyte membrane and the solid electrolyte membrane helps to improve the cycle stability of the solid-state battery.

[0053] Furthermore, the design of the above-mentioned solid electrolyte membrane 10 ensures that the solid electrolyte membrane 10 has good mechanical strength and structural stability, while improving the transport characteristics of lithium ions in the solid electrolyte membrane, thereby inhibiting the growth of lithium dendrites, and further improving the cycle performance and safety performance of the battery.

[0054] In some embodiments, the thickness of the solid electrolyte membrane 10 is 5 micrometers to 40 micrometers.

[0055] In some embodiments, the thickness of the polymer electrolyte membrane 20 is 10 micrometers to 15 micrometers.

[0056] In some embodiments, the polymer electrolyte membrane 20 further includes a polymer electrolyte and a second lithium salt. The mass ratio of the polymer electrolyte to the second lithium salt is (1.5-2.5):1, ensuring that the polymer electrolyte and the second lithium salt have a suitable ratio, so that the polymer electrolyte membrane has good flexibility to effectively construct a stable negative electrode-electrolyte interface, and also has high ionic conductivity for lithium ions.

[0057] In some embodiments, the polymer electrolyte includes, but is not limited to, polymers such as polyvinylidene fluoride.

[0058] In some embodiments, Figure 3 As shown, the composite electrolyte membrane 100 may further include a top solid electrolyte membrane 40 and a bottom solid electrolyte membrane 30. The bottom solid electrolyte membrane 30 is located between the polymer electrolyte membrane 20 and the solid electrolyte membrane 10. The top solid electrolyte membrane 40 is located on the side of the solid electrolyte membrane 10 away from the polymer electrolyte membrane 20. Therefore, the solid electrolyte membrane 10 is an intermediate solid electrolyte membrane between the top solid electrolyte membrane 40 and the bottom solid electrolyte membrane 30.

[0059] In some embodiments, the top solid electrolyte membrane 40 includes a third inorganic electrolyte, and the average particle size of the third inorganic electrolyte is less than or equal to the average particle size of the first inorganic electrolyte. In this way, the average particle size of the third inorganic electrolyte in the top solid electrolyte membrane 40 is small, which is conducive to reducing the surface defects of the top solid electrolyte membrane 40, thereby reducing the interface defects between the composite electrolyte membrane 100 and the electrode, and improving the cycle performance of the battery.

[0060] In some embodiments, the average particle size of the third inorganic electrolyte is equal to the average particle size of the first inorganic electrolyte. Thus, the third inorganic electrolyte and the first inorganic electrolyte can be prepared by the same preparation process, simplifying the formation process of the electrolyte membrane.

[0061] In some embodiments, the average particle size of the third inorganic electrolyte is smaller than the average particle size of the first inorganic electrolyte. In this way, the interface defects between the top solid electrolyte film 40 and the electrode are further reduced, and the cycle performance of the battery is improved.

[0062] In some embodiments, the average particle size of the third inorganic electrolyte is 100 nm to 800 nm. Alternatively, the average particle size of the third inorganic electrolyte is 100 nm to 500 nm.

[0063] In some embodiments, the top solid electrolyte membrane 40 also includes an adhesive. The adhesive may include one or more of polyethylene oxide, polyurethane rubber, polyvinylidene fluoride, poly(vinylidene fluoride-trifluoroethylene), poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene), polyvinylidene fluoride hexafluoropropylene, polyaryl acetylene, polycaprolactone, and polyvinyl butyral. Exemplarily, the adhesive of the top solid electrolyte membrane includes poly(vinylidene fluoride-trifluoroethylene).

[0064] In some embodiments, the top solid electrolyte membrane 40 further includes a third lithium salt. In some embodiments, the third lithium salt may be the same as the first lithium salt to simplify the preparation process of the composite electrolyte membrane.

[0065] In some embodiments, the third lithium salt is selected from one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate, and lithium hexafluorophosphate.

[0066] In some embodiments, the thickness of the top solid electrolyte membrane 40 is less than the thickness of the solid electrolyte membrane 10. When the thicknesses of the top solid electrolyte membrane 40, the solid electrolyte membrane 10 and the bottom solid electrolyte membrane 30 are constant, the solid electrolyte membrane 10 is thicker, which plays a major role in improving the transmission performance of lithium ions and thus improving the cycle performance of the solid-state lithium battery, while the top solid electrolyte membrane 40 plays an auxiliary role in reducing the interface defects between the composite electrolyte membrane 100 and the electrode and thus improving the cycle performance of the solid-state lithium battery.

[0067] In some embodiments, in the top solid electrolyte membrane, the mass ratio of the third inorganic electrolyte, the binder, and the third lithium salt is (80-90): (8-15): (1-5).

[0068] In some embodiments, the mass proportion of the third lithium salt in the top solid electrolyte membrane 40 is greater than the mass proportion of the first lithium salt in the solid electrolyte membrane 10. This is beneficial to improve the ionic conductivity of the top solid electrolyte membrane 40 to lithium ions.

[0069] In some embodiments, the thickness of the top solid electrolyte film 40 is 5 microns to 8 microns.

[0070] In some embodiments, the bottom solid electrolyte membrane 30 includes a fourth inorganic electrolyte, and the average particle size of the fourth inorganic electrolyte is greater than or equal to the average particle size of the second inorganic electrolyte. In this way, the average particle size of the fourth inorganic electrolyte in the bottom solid electrolyte membrane 30 is large, and the bottom solid electrolyte membrane 30 has good mechanical strength. In addition, since the bottom solid electrolyte membrane 30 is located between the polymer electrolyte membrane 20 and the solid electrolyte membrane 10, the bottom solid electrolyte membrane 30 provides good support for the polymer electrolyte membrane 20, the solid electrolyte membrane 10 and the top solid electrolyte membrane 40, further improving the mechanical strength of the entire electrolyte membrane.

[0071] In some embodiments, the fourth inorganic electrolyte may have an average particle size of 1 μm to 20 μm.

[0072] In some embodiments, the average particle size of the fourth inorganic electrolyte may be equal to the average particle size of the second inorganic electrolyte. In this case, the average particle size of the fourth inorganic electrolyte may be 1 μm to 10 μm.

[0073] In some embodiments, the average particle size of the fourth inorganic electrolyte may be greater than the average particle size of the second inorganic electrolyte, further improving the mechanical properties of the bottom solid electrolyte membrane 30. At this time, the average particle size of the fourth inorganic electrolyte may be 10 μm to 20 μm.

[0074] It should be noted that, when the average particle size of the third inorganic electrolyte is smaller than the average particle size of the first inorganic electrolyte, and the average particle size of the fourth inorganic electrolyte is larger than the average particle size of the second inorganic electrolyte, the particle size of the inorganic electrolyte increases from the top solid electrolyte membrane 40 to the bottom solid electrolyte membrane 30, which also helps to improve the overall density of the electrolyte membrane.

[0075] In some embodiments, the bottom solid electrolyte membrane 30 also includes an adhesive. The adhesive may include one or more of polyethylene oxide, polyurethane rubber, polyvinylidene fluoride, poly(vinylidene fluoride-trifluoroethylene), poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene), polyvinylidene fluoride hexafluoropropylene, polyaryl acetylene, polycaprolactone, and polyvinyl butyral. Exemplarily, the adhesive of the top solid electrolyte membrane includes poly(vinylidene fluoride-trifluoroethylene).

[0076] In some embodiments, the bottom solid electrolyte membrane 30 further includes a fourth lithium salt. In some embodiments, the fourth lithium salt may be the same as the first lithium salt to simplify the preparation process of the composite electrolyte membrane.

[0077] In some embodiments, the fourth lithium salt is selected from one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate, and lithium hexafluorophosphate.

[0078] In some embodiments, the thickness of the bottom solid electrolyte membrane 30 may be greater than the thickness of the solid electrolyte membrane 10. In this way, the bottom solid electrolyte membrane 30 can better improve the mechanical strength of the electrolyte.

[0079] In other embodiments, the thickness of the bottom solid electrolyte membrane 30 may be less than the thickness of the solid electrolyte membrane 10, and greater than the thickness of the top solid electrolyte membrane 40. In this way, when the thicknesses of the top solid electrolyte membrane 40, the solid electrolyte membrane 10, and the bottom solid electrolyte membrane 30 are constant, the thickness of the solid electrolyte membrane 10 is thicker, which plays a major role in improving the cycle performance of the solid-state lithium battery, and the bottom solid electrolyte membrane 30 and the top solid electrolyte membrane 40 play an auxiliary role in improving the cycle performance of the solid-state lithium battery.

[0080] In some embodiments, the thickness of the bottom solid electrolyte membrane 30 is 12 micrometers to 15 micrometers.

[0081] In some embodiments, in the bottom solid electrolyte membrane 30 , the mass ratio of the fourth inorganic electrolyte, the binder, and the fourth lithium salt is (80-90): (8-15): (1-5).

[0082] In some embodiments, the mass proportion of the fourth lithium salt in the bottom solid electrolyte membrane 30 is greater than the mass proportion of the first lithium salt in the solid electrolyte membrane 10. This is beneficial to improve the ionic conductivity of the bottom solid electrolyte membrane 30 to lithium ions.

[0083] In some embodiments, the bottom solid electrolyte membrane 30 and the top solid electrolyte membrane 40 may be formed on opposite sides of the solid electrolyte membrane 10 by a tape casting process.

[0084] In a fourth aspect, the present application also provides a method for preparing a composite electrolyte membrane, comprising: forming a solid electrolyte membrane; forming a polymer electrolyte membrane; The solid electrolyte membrane and the polymer electrolyte membrane are stacked to obtain a composite electrolyte membrane.

[0085] In some embodiments, forming a solid electrolyte membrane includes: Providing the electrolyte composition and a first solvent; Dissolving each component of the electrolyte composition in a first solvent to obtain a first slurry; An initial solid electrolyte membrane is formed by using the first slurry, and the first solvent is removed to obtain a solid electrolyte membrane.

[0086] Some embodiments of the present application adopt a wet method to prepare a solid electrolyte membrane, thereby improving the dispersion uniformity of each component in the electrolyte composition and improving the uniformity of the performance of the solid electrolyte membrane.

[0087] In some embodiments, an initial solid electrolyte membrane may be formed on a release film, and the solid electrolyte membrane may be obtained after removing the first solvent.

[0088] In some embodiments, an electrolyte composition is provided, comprising: providing an initial inorganic electrolyte; placing the initial inorganic electrolyte and the dispersant in a ball milling jar and performing a first ball milling treatment to obtain a second inorganic electrolyte; Taking out a portion of the second inorganic electrolyte, and subjecting the remaining second inorganic electrolyte to a second ball milling process to obtain a first inorganic electrolyte; Part of the second inorganic electrolyte and the first inorganic electrolyte are mixed uniformly to obtain an inorganic electrolyte.

[0089] In some embodiments, the conditions of the first ball milling treatment include: a rotation speed of 400 r / min to 600 r / min, and a time of 12 h to 20 h.

[0090] In some embodiments, the conditions of the second ball milling treatment include: a rotation speed of 400 r / min to 600 r / min, and a time of 30 h to 34 h.

[0091] In some embodiments, the dispersant includes but is not limited to alcohol solvents, and the alcohol solvents include but are not limited to isopropanol.

[0092] In some embodiments, the first solvent includes an amide compound. The amide compound includes, but is not limited to, at least one of N,N-dimethylformamide, N-methylpyrrolidone, caprolactam, and N-ethylpyrrolidone. Exemplarily, the first solvent includes N,N-dimethylformamide.

[0093] In some embodiments, the electrolyte composition further includes a first lithium salt, an ionic liquid, a binder, and a fluorine-containing ester compound.

[0094] In some embodiments, dissolving the components of the electrolyte composition in a first solvent includes: dissolving an inorganic electrolyte, an ionic liquid, a first lithium salt, a binder, and a fluorine-containing ester compound in the first solvent.

[0095] In some embodiments, forming a polymer electrolyte membrane includes: providing a polymer electrolyte, a second lithium salt, and a second solvent; dissolving the polymer electrolyte and the second lithium salt in a second solvent to obtain a second slurry; The second slurry is used to form an initial polymer electrolyte membrane, and the second solvent is removed to obtain a polymer electrolyte membrane.

[0096] Some embodiments of the present application adopt a wet method to prepare a polymer electrolyte membrane, thereby improving the dispersion uniformity of each component in the polymer electrolyte and improving the uniformity of the performance of the solid electrolyte membrane.

[0097] In some embodiments, the mass ratio of the polymer electrolyte to the second lithium salt is (1.5-2.5):1, ensuring that the polymer electrolyte and the second lithium salt have a suitable ratio, so that the polymer electrolyte membrane has good flexibility and high ionic conductivity to lithium ions.

[0098] In some embodiments, the mass ratio of the polymer electrolyte to the second solvent is (1.5-2.5):(8-12), so as to ensure that the polymer electrolyte can be fully dissolved in the second solvent.

[0099] In some embodiments, the polymer electrolyte includes, but is not limited to, polymers such as polyvinylidene fluoride.

[0100] In some embodiments, the second lithium salt may be the same as the first lithium salt to simplify the preparation process of the composite electrolyte membrane.

[0101] In some embodiments, the second lithium salt is selected from one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate, and lithium hexafluorophosphate.

[0102] In some embodiments, the second solvent includes an amide compound. The amide compound includes, but is not limited to, at least one of N,N-dimethylformamide, N-methylpyrrolidone, caprolactam, and N-ethylpyrrolidone. Exemplarily, the first solvent includes N,N-dimethylformamide.

[0103] In some embodiments, the method for preparing the composite electrolyte membrane further comprises: Dissolving a third inorganic electrolyte, a third lithium salt and a binder in a third solvent and mixing them evenly to obtain a third slurry; The third slurry is used to form an initial top solid electrolyte membrane, and the third solvent is removed to obtain a top solid electrolyte membrane.

[0104] In some embodiments, after forming the solid electrolyte membrane, an initial top solid electrolyte membrane may be formed on the solid electrolyte membrane. Thus, during the process of forming the third slurry on the solid electrolyte membrane, the third inorganic electrolyte in the third slurry at least fills part of the gap on the surface of the solid electrolyte membrane, so that the top solid electrolyte membrane is stacked on the solid electrolyte membrane, while improving the density of the solid electrolyte membrane.

[0105] In some embodiments, the method for preparing the composite electrolyte membrane further comprises: Dissolving a fourth inorganic electrolyte, a fourth lithium salt and a binder in a fourth solvent and mixing them evenly to obtain a fourth slurry; The fourth slurry is used to form an initial bottom solid electrolyte membrane, and the fourth solvent is removed to obtain a bottom solid electrolyte membrane.

[0106] In some embodiments, an initial bottom solid electrolyte film may be formed on a release layer.

[0107] In some embodiments, after forming the bottom solid electrolyte membrane, the initial solid electrolyte membrane can be formed on the bottom solid electrolyte membrane. In this way, during the process of forming the first slurry on the bottom solid electrolyte membrane, the first inorganic electrolyte in the first slurry can at least fill the gap on the surface of the bottom solid electrolyte membrane, so that the solid electrolyte membrane is stacked on the bottom solid electrolyte membrane, while improving the density of the bottom solid electrolyte membrane.

[0108] In a fifth aspect, an embodiment of the present application further provides a battery. The battery comprises a positive electrode, a negative electrode and the composite electrolyte membrane. The composite electrolyte membrane is located between the positive electrode and the negative electrode. The polymer electrolyte membrane is located between the solid electrolyte membrane and the negative electrode.

[0109] In some embodiments, the material of the positive electrode includes one or more of lithium nickel manganese oxide, lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, and lithium nickel cobalt manganese oxide.

[0110] In some embodiments, the negative electrode includes one or more of a metallic lithium negative electrode, a metallic lithium alloy negative electrode, a graphite negative electrode, a silicon-based negative electrode, a silicon-graphite composite negative electrode, and a copper foil lithium-free negative electrode.

[0111] The following is a detailed description with reference to specific embodiments.

[0112] In the following examples, polyethylene oxide (PEO) (relative molecular weight of 7,900,000) was purchased from MacLean's P888666, P (VDF-TrFE) was purchased from Gadal (the molar ratio of VDF-TrFE was 80:20, product number JD200721095524), and other raw materials were commercially available.

[0113] Example 1 This embodiment provides a method for preparing a solid electrolyte membrane. The method includes preparing an inorganic electrolyte and a solid electrolyte membrane. The specific methods of the two are as follows.

[0114] (1) Preparation of inorganic electrolyte Weigh an appropriate amount of Li7La3Zr2O with an original particle size of 100 μm 12 (LLZO) powder and isopropanol (dispersant) are placed in a ball mill, and the mass ratio of LLZO, isopropanol and ball milling beads in the ball mill is 2:3:10; The original particle size of Li7La3Zr2O is 100 μm. 12 Ball milling was performed at a rotation speed of 500 r for 18 h to obtain a second inorganic electrolyte with an average particle size of 1 μm to 10 μm; The second inorganic electrolyte with a particle size of 1 μm to 10 μm is ball-milled at a rotation speed of 500 r for 36 h to obtain a first inorganic electrolyte with an average particle size of 300 nm to 800 nm; The first inorganic electrolyte and the second inorganic electrolyte are uniformly mixed in a mass ratio of 8:2 to obtain an inorganic electrolyte.

[0115] (2) Preparation of solid electrolyte membrane 5.22 g (87%) of the above-mentioned uniformly mixed inorganic electrolyte, 0.06 g (1%) of lithium bis(fluorosulfonyl)imide (LiFSI), 0.045 g (0.75%) of 1-benzyl-3-methylimidazole bis(trifluoromethylsulfonyl)imide salt (BzmimTFSI), and 0.045 g (0.75%) of 1-ethyl-3-methylimidazole bis(trifluoromethylsulfonyl)imide salt ([EMIM][TFSI]) were added to 9 g of N,N-dimethylformamide (DMF), and stirred at 1500 r for 10 minutes by a stirrer to completely disperse the inorganic electrolyte, thereby obtaining a first mixture; Next, 0.12 g (2%) of hexafluorobutyl methacrylate (TFBMA) was added to the first mixture, and the mixture was stirred at 1500 rpm for 10 minutes to completely disperse the mixture, thereby obtaining a second mixture. Then, 0.09 g (1.5%) of polyethylene oxide (PEO) was added to the second mixture, and the mixture was stirred at 1500 rpm for 10 minutes to completely disperse the mixture, thereby obtaining a third mixture. Then, 0.42 g (7%) of poly(vinylidene fluoride and trifluoroethylene) copolymer P(VDF-TrFE) was added to the third mixture, and stirred at 1500r for 10 minutes by a stirrer, and degassed by a degassing machine for 2 minutes to obtain a first slurry; Finally, the first slurry was scraped onto the PET release film with a 250 μm scraper to form an initial solid electrolyte membrane, and then vacuum dried to obtain a solid electrolyte membrane with a thickness of 30 μm.

[0116] Example 2 This embodiment provides a method for preparing a solid electrolyte membrane. Embodiment 2 is substantially similar to Embodiment 1, except that, in the process of preparing the inorganic electrolyte, the first inorganic electrolyte and the second inorganic electrolyte are uniformly mixed in a mass ratio of 7:3.

[0117] Example 3 This embodiment provides a method for preparing a solid electrolyte membrane. Embodiment 3 is substantially similar to Embodiment 1, except that, in the process of preparing the inorganic electrolyte, the first inorganic electrolyte and the second inorganic electrolyte are uniformly mixed in a mass ratio of 6:4.

[0118] Example 4 This embodiment provides a method for preparing a solid electrolyte membrane. Embodiment 4 is basically similar to Embodiment 1, except that, in the process of preparing the solid electrolyte membrane, "0.045 g 1-benzyl-3-methylimidazole bis(trifluoromethylsulfonyl)imide and 0.045 g 1-ethyl-3-methylimidazole bis(trifluoromethylsulfonyl)imide" is replaced with 0.09 g (1.5%) 1-benzyl-3-methylimidazole bis(trifluoromethylsulfonyl)imide.

[0119] Example 5 This embodiment provides a method for preparing a solid electrolyte membrane. Embodiment 5 is basically similar to Embodiment 1, except that, in the process of preparing the solid electrolyte membrane, "0.045 g 1-benzyl-3-methylimidazole bis(trifluoromethylsulfonyl)imide and 0.045 g 1-ethyl-3-methylimidazole bis(trifluoromethylsulfonyl)imide" is replaced with 0.09 g (1.5%) 1-ethyl-3-methylimidazole bis(trifluoromethylsulfonyl)imide.

[0120] Example 6 This embodiment provides a method for preparing a solid electrolyte membrane. Embodiment 6 is basically similar to Embodiment 1, except that, in the process of preparing the solid electrolyte membrane, the step of "adding 0.12 g (2%) hexafluorobutyl methacrylate to the above-mentioned first mixture" is omitted.

[0121] Example 7 This embodiment provides a method for preparing a solid electrolyte membrane. Embodiment 7 is basically similar to Embodiment 1, except that, in the process of preparing the solid electrolyte membrane, "adding 0.09 g (1.5%) of polyethylene oxide (PEO) to the second mixture and adding 0.42 g (7%) of PVDF-TrEE binder to the third mixture" is replaced by "adding 0.51 g (8.5%) of PVDF-TrFE binder".

[0122] Example 8 The present embodiment provides a method for preparing a solid electrolyte membrane. Embodiment 8 is substantially similar to Embodiment 1, except that, in the process of preparing the solid electrolyte membrane, “adding 0.09 g (1.5%) of polyethylene oxide (PEO) to the second mixture and adding 0.42 g (7%) of PVDF-TrFE binder to the third mixture” is replaced by “adding 0.03 g (0.5%) of polyethylene oxide (PEO) to the second mixture and adding 0.48 g (8%) of PVDF-TrFE binder to the third mixture”.

[0123] Comparative Example 1 Comparative Example 1 is substantially similar to Example 1, except that "5.22 g of inorganic electrolyte" in the preparation of the solid electrolyte membrane in Example 1 is replaced by "5.22 g of the first inorganic electrolyte".

[0124] Comparative Example 2 Comparative Example 2 is substantially similar to Example 1, except that "5.22 g of inorganic electrolyte" in the preparation of the solid electrolyte membrane in Example 1 is replaced by "5.22 g of a second inorganic electrolyte".

[0125] Comparative Example 3 Comparative Example 3 is substantially similar to Example 1, except that “the first inorganic electrolyte and the second inorganic electrolyte are uniformly mixed in a mass ratio of 8:2” in Example 1 is replaced by “the first inorganic electrolyte and the second inorganic electrolyte are uniformly mixed in a mass ratio of 4:6”.

[0126] The ionic conductivities of Examples 1 to 8 and Comparative Examples 1 to 3 were tested respectively, and the film-forming properties of the solid electrolyte membranes in Examples 1 to 8 and Comparative Examples 1 to 3 were observed. The results are shown in Table 1.

[0127] The ionic conductivity is measured by cutting the solid electrolyte membrane into discs with a diameter of 16 mm, sandwiching the discs between two stainless steel gaskets to assemble a symmetrical battery, and then connecting the electrochemical workstation to perform impedance testing to obtain the bulk impedance value of the sample to be tested.

[0128] The ionic conductivity is calculated according to the formula σ = l / (AR), the unit is S / cm; l is the thickness of the solid electrolyte membrane, the unit is cm; A is the area of ​​the solid electrolyte membrane, the unit is cm 2 ; R is the body impedance of the sample to be tested, in Ω.

[0129] Table 1

[0130] It can be seen from Table 1 that the solid electrolyte membranes of Examples 1 to 8 have good film-forming properties and no cracks, and also have high ionic conductivity. Therefore, in the electrolyte composition provided in the embodiments of the present application, the first inorganic electrolyte with an average particle size of 300nm to 800nm ​​and the second inorganic electrolyte with an average particle size of 1μm to 10μm are compounded in an appropriate mass percentage, which not only improves the ionic conductivity of the electrolyte membrane, but also improves the problem of poor film-forming properties and cracks in the electrolyte during the formation process.

[0131] Moreover, the solid electrolyte membrane of Comparative Example 1 has poor film-forming properties and many cracks, mainly because the inorganic electrolytes in Comparative Example 1 are all the first inorganic electrolytes with a smaller average particle size, and the first inorganic electrolyte with a smaller average particle size is not conducive to film formation. The ionic conductivity of the solid electrolyte membrane of Comparative Example 2 is relatively small, mainly because the inorganic electrolytes in Comparative Example 2 are all the second inorganic electrolytes with a larger average particle size, and the second inorganic electrolyte with a larger average particle size is not conducive to improving ionic conductivity. The ionic conductivity of the solid electrolyte membrane of Comparative Example 3 is relatively small, mainly because the mass proportion of the second inorganic electrolyte in Comparative Example 3 is greater than the mass proportion of the first inorganic electrolyte, and the second inorganic electrolyte is not conducive to improving ionic conductivity.

[0132] In addition, it can be seen from the combination of Examples 1 to 3 that as the mass proportion of the first inorganic electrolyte having a smaller average particle size in the inorganic electrolyte increases, the ionic conductivity of the solid electrolyte membrane increases.

[0133] Combining Example 1 with Example 4 and Example 5, it can be seen that the ionic conductivity of the solid electrolyte membrane in Example 1 is greater than the ionic conductivity of the solid electrolyte membrane in Example 4 and Example 5. Therefore, the 1-benzyl-3-methylimidazolium cation of the first ionic liquid and the 1-ethyl-3-methylimidazolium cation of the second ionic liquid are compounded in a suitable ratio to improve the ionic conductivity of the solid electrolyte membrane.

[0134] Combining Example 1 and Example 6, it can be seen that the ionic conductivity of the solid electrolyte membrane in Example 1 is greater than the ionic conductivity of the solid electrolyte membrane in Example 6. Therefore, hexafluorobutyl methacrylate is introduced into the solid electrolyte, and hexafluorobutyl methacrylate can improve the ionic conductivity of the solid electrolyte membrane.

[0135] Combining Example 1, Example 7 and Example 8, it can be seen that the ionic conductivity of the solid electrolyte membrane in Example 1 and Example 8 is greater than the ionic conductivity of the solid electrolyte membrane in Example 7. Therefore, the ionic conductivity of the solid electrolyte membrane can be improved by compounding polyethylene oxide and ethyl trifluoroacetate-modified polyvinylidene fluoride in a suitable ratio.

[0136] Application Example 1 This application example provides a composite electrolyte membrane and a battery, and the preparation method is as follows: 0.5 g of the second lithium salt LiFSI and 1.0 g of the polymer electrolyte PVDF were dissolved in 10 g of the second solvent DMF, and stirred at room temperature for 12 h to prepare a second mixed solution, and a 250 μm scraper was used to scrape on a glass plate by a solution casting-drying method, and dried at 80° C. to obtain a polymer electrolyte membrane with a thickness of 10 μm; Align and stack the solid electrolyte membrane of Example 1 and the polymer electrolyte membrane of this example to obtain a composite electrolyte membrane; Under the inert atmosphere of a glove box, the positive electrode, composite electrolyte membrane and negative electrode were assembled in sequence. The solid electrolyte membrane of the composite electrolyte membrane was arranged close to the positive electrode, and the polymer electrolyte membrane was arranged close to the negative electrode. The assembly was completed by pressing at 800 kPa for 5 s to obtain a Li||NMC811 battery.

[0137] Application Examples 2 to 8 Application Examples 2 to 8 are basically the same as Application Example 1, except that the solid electrolyte membrane of Example 1 is replaced by the solid electrolyte membrane of Examples 2 to 8 in Application Examples 2 to 8, respectively. Among them, the solid electrolyte in Application Example 2 is the solid electrolyte membrane of Example 2. The solid electrolyte in Application Example 3 is the solid electrolyte membrane of Example 3. The solid electrolyte in Application Example 4 is the solid electrolyte membrane of Example 4. The solid electrolyte in Application Example 5 is the solid electrolyte membrane of Example 5. The solid electrolyte in Application Example 6 is the solid electrolyte membrane of Example 6. The solid electrolyte in Application Example 7 is the solid electrolyte membrane of Example 7. The solid electrolyte in Application Example 8 is the solid electrolyte membrane of Example 8.

[0138] Application Example 9 The application example is basically the same as the application example 1, except that the composite electrolyte membrane in the application example 9 further includes a top solid electrolyte membrane and a bottom solid electrolyte membrane. The bottom solid electrolyte membrane is located between the polymer electrolyte membrane and the solid electrolyte membrane. The top solid electrolyte membrane is located on the side of the solid electrolyte membrane away from the polymer electrolyte membrane. In addition, the thickness of the solid electrolyte membrane is 10 microns.

[0139] The preparation method of the top solid electrolyte membrane is as follows: 5.4 g (90%) of the third inorganic electrolyte with an average particle size of 300 nm to 800 nm obtained by grinding in Example 1, 0.12 g (2%) of the third lithium salt LiFSI and 0.48 g (8%) of the PVDF-TrFE binder were dissolved in 10 g of the third solvent DMF, mixed evenly, and then a 7-micron top solid electrolyte membrane was formed on the solid electrolyte membrane by a tape casting film forming technology.

[0140] The preparation method of the bottom solid electrolyte membrane is as follows: 5.4 g (90%) of the fourth inorganic electrolyte with an average particle size of 1 μm to 10 μm obtained by grinding in Example 1, 0.12 g (2%) of the fourth lithium salt LiFSI and 0.48 g (8%) of PVDF-TrFE binder were dissolved in 10 g of the fourth solvent DMF, mixed evenly, and then a 15-micron bottom solid electrolyte membrane was formed on the solid electrolyte membrane by a tape casting film forming technology.

[0141] Application Comparative Examples 1~3 Application Comparative Examples 1 to 3 are basically the same as Application Example 1, except that the solid electrolyte membrane of Example 1 is replaced by the solid electrolyte membrane of Comparative Examples 1 to 3 in Application Comparative Examples 1 to 3, respectively. Among them, the solid electrolyte in Application Comparative Example 1 is the solid electrolyte membrane of Comparative Example 1. The solid electrolyte in Application Comparative Example 2 is the solid electrolyte membrane of Comparative Example 2. The solid electrolyte in Application Comparative Example 3 is the solid electrolyte membrane of Comparative Example 3.

[0142] The ionic conductivity of the composite electrolyte membranes of Application Examples 1 to 9 and Application Comparative Examples 1 to 3, as well as the cycle life and capacity retention rate of the batteries were tested respectively, and the data results are shown in Table 2.

[0143] Among them, the test method for cycle life and capacity retention rate (cycle curve) is: charge the battery to 4.2V at 0.33C constant current and constant voltage at 25°C, and then discharge it to 3.0V at 0.5C constant current. This is one cycle, and the remaining capacity is the capacity retention rate. Compare the number of cycles or capacity retention rates of each battery.

[0144] Table 2

[0145] It can be seen from Table 2 that the composite electrolyte membranes of Application Example 1 to Application Example 9 have high ionic conductivity compared to the composite electrolyte membranes of Application Example 2 and Application Example 3. Moreover, compared to the batteries of Application Example 1 to Application Example 3, the cycle life of the batteries of Application Example 1 to Application Example 9 is not only significantly improved, but also the capacity retention rate can be maintained at 80% after 89 or more charge and discharge cycles. Therefore, the electrolyte composition provided in the embodiments of the present application can improve the ionic conductivity of the composite electrolyte membrane, and improve the cycle life and capacity retention rate of the battery.

[0146] The description of the above embodiments is only used to help understand the technical solutions and core ideas of the present application. Ordinary technical personnel in this field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some of the technical features therein with equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. An electrolyte composition, characterized in that Comprising an inorganic electrolyte, the inorganic electrolyte comprising: A first inorganic electrolyte, wherein the average particle size of the first inorganic electrolyte is 300 nm to 800 nm; A second inorganic electrolyte, wherein the average particle size of the second inorganic electrolyte is 1 μm to 10 μm; Among the inorganic electrolytes, the mass percentage of the first inorganic electrolyte is 60% to 80%, and the mass percentage of the second inorganic electrolyte is 20% to 40%.

2. The electrolyte composition according to claim 1, characterized in that It also includes an ionic liquid, which includes a first ionic liquid and a second ionic liquid, the first ionic liquid includes a 1-benzyl-3-methylimidazolium cation, the second ionic liquid includes a 1-ethyl-3-methylimidazolium cation, and the mass ratio of the inorganic electrolyte, the first ionic liquid and the second ionic liquid is (80~90):(0.6~0.9):(0.6~0.9).

3. The electrolyte composition according to claim 2, characterized in that The anion of the first ionic liquid and the anion of the second ionic liquid are each independently selected from one or more of bis(trifluoromethylsulfonyl)imide, bis(fluorosulfonyl)imide, bistrifluoromethylsulfonate and trifluoromethylsulfonate.

4. The electrolyte composition according to claim 1, characterized in that The electrolyte composition further includes a first lithium salt, wherein the first lithium salt includes a fluorine-containing lithium salt, and the mass ratio of the fluorine-containing lithium salt to the inorganic electrolyte is 1:(80-90); and / or, The electrolyte composition further comprises a fluorine-containing ester compound, and the mass ratio of the fluorine-containing ester compound to the inorganic electrolyte is (1.5-2.5):(80-90).

5. The electrolyte composition according to claim 4, characterized in that The fluorine-containing ester compound includes hexafluorobutyl methacrylate; and / or, The fluorine-containing lithium salt is selected from one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate and lithium hexafluorophosphate.

6. The electrolyte composition according to claim 1, characterized in that It also includes a binder, which includes polyethylene oxide and a fluorine-containing polymer. The mass ratio of the inorganic electrolyte, the polyethylene oxide and the fluorine-containing polymer is (80-90): (1-2): (6-8).

7. The electrolyte composition according to claim 6, characterized in that The fluorine-containing polymer is selected from one or more of polyvinylidene fluoride, poly(vinylidene fluoride-trifluoroethylene) and poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene); and / or, The weight average molecular weight of the fluorine-containing polymer is 450,000 to 1,100,000; and / or The weight average molecular weight of the polyethylene oxide is 7,500,000-8,500,000.

8. The electrolyte composition according to claim 1, characterized in that The inorganic electrolyte includes one or more of a perovskite-type material, a NASICON-type material, and a garnet-type material.

9. A solid electrolyte membrane, characterized in that: The electrolyte composition comprises the electrolyte composition according to any one of claims 1 to 8.

10. A composite electrolyte membrane, characterized in that: The invention comprises the solid electrolyte membrane and a polymer electrolyte membrane as claimed in claim 9, wherein the polymer electrolyte membrane is stacked with the solid electrolyte membrane, wherein the polymer electrolyte membrane comprises a polymer electrolyte.

11. A method for preparing a composite electrolyte membrane as claimed in claim 10, characterized in that: include: forming a solid electrolyte membrane; forming a polymer electrolyte membrane; The solid electrolyte membrane and the polymer electrolyte membrane are stacked to obtain the composite electrolyte membrane.

12. The method for preparing a composite electrolyte membrane according to claim 11, characterized in that: The forming of the solid electrolyte membrane comprises: Providing an electrolyte composition according to any one of claims 1 to 8 and a first solvent; dissolving each component of the electrolyte composition in the first solvent to obtain a first slurry; The first slurry is used to form an initial solid electrolyte membrane, and the first solvent is removed to obtain the solid electrolyte membrane.

13. The method for preparing a composite electrolyte membrane according to claim 11, characterized in that: The forming of the polymer electrolyte membrane comprises: providing a polymer electrolyte, a second lithium salt, and a second solvent; dissolving the polymer electrolyte and the second lithium salt in the second solvent to obtain a second slurry; The second slurry is used to form an initial polymer electrolyte membrane, and the second solvent is removed to obtain the polymer electrolyte membrane.

14. A battery, characterized in that: include: positive electrode; negative electrode; as well as The composite electrolyte membrane according to claim 10, wherein the composite electrolyte membrane is located between the positive electrode and the negative electrode, and the polymer electrolyte membrane is located between the solid electrolyte membrane and the negative electrode.

Citation Information

Patent Citations

  • Manufacturing method for electrode for all-solid-state battery and manufacturing method for all solid-state-battery

    CN110235284A

  • Solid electrolyte and preparation method and application thereof

    CN111554970A

  • Inorganic solid electrolyte-containing composition, all-solid-state secondary battery sheet, all-solid-state secondary battery, and method for producing inorganic solid electrolyte-containing composition, all-solid-state secondary battery sheet, and all-solid-state secondary battery

    CN114450832A

  • Electrode for all-solid-state battery, all-solid-state battery, and method for producing same

    CN116741933A

  • Composition, ceramic electrolyte thin film, preparation method of ceramic electrolyte thin film, composite thin film and application of composite thin film

    CN118156589A